Hubungan Pengetahuan, Sarana Prasarana, dan Pengawasan Terhadap Perilaku Pencegahan Covid-19 - Nina; Riyanti, Fitri Fajar (MPI Press, 2022)
Introduction: West Java Province ranks first with a total of 270,711 cases and Depok City is the highest city with a total of 45,663 cases. The contributing factors are the positivity rate above 20%, the increase in specimens examined, and data delays. Based on a preliminary study in April 2021, it was found that 50% of employees had poor knowledge, 20% of employees stated that infrastructure was inadequate, and there was no regular supervision. The impact of low levels of Covid-19 prevention behavior is an increase in Covid-19 transmission. Objective: To determine the relationship between knowledge, infrastructure, and supervision of Covid-19 prevention behavior among School X employees in Depok City in 2021. Methods: Quantitative research with a cross-sectional approach. The research sample of 120 employees used a questionnaire. Univariate and bivariate analysis with chi-square test. Results: There is a relationship between knowledge (0.000), infrastructure (0.000) and supervision (0.000) with Covid-19 prevention behavior among School X Employees in Depok City in 2021. Conclusion: Knowledge, availability of infrastructure and supervision of school X in Depok City in 2021 are in the good category, although there are still some that are not good. So it needs to be improved because PTMT will be carried out soon and employees are role models for students.